Rethinking Policy Design: Integrating Traditional, Market-oriented and Corporatist Career Management Policy Instruments across South African Public Service Departments - Shereen Sikwela; Melvin Diedericks (E-Journal of Humanities, Arts and Social Sciences)
Policy design gained popularity in the 1970s, thus proliferating extensive scholarly research within the field. This persistent trajectory is sustained by a significant emphasis on integrating diverse instruments within contemporary democratic and governance contexts. Despite the relevance of instrument mix, the integration of traditional, corporatist, and market-oriented policy instruments still needs to be explored in the African context, particularly in career management. This study addressed this gap by investigating the integration of these diverse paradigms through insights from the metaphysical foundations of governance models alongside the empirical data gathered from the stakeholders at the North West Province Departments of Cooperative Governance Traditional Affairs and Human Settlements. Findings revealed a divergence of policy design approaches, culminating in the misalignment of policy instruments in career management. This misalignment hampers the integration of employee development objectives with Public Service goals. Findings revealed that the underlying cause of this deficiency is the misalignment of NATO instruments. Therefore key stakeholders in both departments should realign policy instruments and enhance targeted capability building. The study contributes to public administration theory, policy design, career management, and integrative governance by prioritising the alignment of policy instruments, thereby bridging the gap between organisational and employee developmental goals. This collaborative approach reveals the potentiality of integrative governance in harmonising diverse policy instruments in public organisations.